1978
DOI: 10.2466/pms.1978.46.2.531
|View full text |Cite
|
Sign up to set email alerts
|

On the Validity of Hypotheses Derived from the Rorschach: III. The Relationship between Shading and Anxiety

Abstract: Research was reviewed in an attempt to assess the validity of the hypothesis that shading on the Rorschach is related to anxiety. This research turned out to be replete with inconsistent and contradictory findings. The reasons for this are discussed. However, as a consequence of the kind of research that has been conducted in this area, we are unable to draw any conclusions except that we need more research. The methodological and epistemological issues in this research are discussed with the hope of providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a series of brief focused literature reviews, Frank concluded that there are no well-demonstrated relations between (a) color responses and emotional expression or control (Frank, 1976, 1993c), (b) achromatic color responses (C') and depression (Frank, 1993a), (c) shading responses and anxiety (Frank, 1978, 1993d), (d) space responses and oppositionality or hostility (Frank, 1993e), (e) movement responses and intelligence or degree of “inner life” (Frank, 1979b, 1993b, 1997), or (f) Rorschach content and aggressive behavior (Frank, 1994b). On the other hand, Frank concluded that good form quality (F+%) (g) is related to psychotherapy outcome (Frank, 1993f) and (h) differentiates psychotic from nonpsychotic patients, schizophrenic from non-schizophrenic patients, and process schizophrenics from reactive schizophrenics (Frank, 1979, 1980, 1994a).…”
Section: Rorschach Inkblot Testmentioning
confidence: 99%
“…In a series of brief focused literature reviews, Frank concluded that there are no well-demonstrated relations between (a) color responses and emotional expression or control (Frank, 1976, 1993c), (b) achromatic color responses (C') and depression (Frank, 1993a), (c) shading responses and anxiety (Frank, 1978, 1993d), (d) space responses and oppositionality or hostility (Frank, 1993e), (e) movement responses and intelligence or degree of “inner life” (Frank, 1979b, 1993b, 1997), or (f) Rorschach content and aggressive behavior (Frank, 1994b). On the other hand, Frank concluded that good form quality (F+%) (g) is related to psychotherapy outcome (Frank, 1993f) and (h) differentiates psychotic from nonpsychotic patients, schizophrenic from non-schizophrenic patients, and process schizophrenics from reactive schizophrenics (Frank, 1979, 1980, 1994a).…”
Section: Rorschach Inkblot Testmentioning
confidence: 99%